Primer composition, negative electrode and secondary battery comprising the primer composition, and method for preparing negative electrode

By adding a thickener containing hydroxyl and carboxylic functional groups to the negative electrode primer composition of the lithium secondary battery, the poor process problems caused by low viscosity of the primer layer are solved, and the effect of improving electrode surface cracks and pinholes, improving battery resistance and fast charging performance is achieved.

CN116554737BActive Publication Date: 2025-04-18SK ON CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210524914.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-01-27
Filing Date
2022-05-13
Publication Date
2025-04-18
Estimated Expiration
2042-05-13

AI Technical Summary

Technical Problem

When preparing the negative electrode of the lithium secondary battery, the low viscosity of the primer layer leads to poor process, such as cracks on the electrode surface or poor pinholes, which affects the performance and reliability of the battery.

Method used

The primer composition containing a thickener containing a hydroxyl and carboxyl functional group is used to increase the cohesion of the adhesive by adding a thickener to the primer composition, and the pinhole problem is reduced by controlling the residue content of the thickener to be less than 0.05% by weight.

Benefits of technology

The frequency of cracks and pinholes on the electrode surface is significantly improved, the interface adhesion of the negative electrode is improved, the resistance and fast charging performance of the secondary battery are enhanced, and the defect rate in the preparation process is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003643807760000131
    Figure BDA0003643807760000131
  • Figure BDA0003643807760000141
    Figure BDA0003643807760000141
  • Figure BDA0003643807760000151
    Figure BDA0003643807760000151
Patent Text Reader

Abstract

The present invention provides a primer composition, a negative electrode and a secondary battery comprising the primer composition, and a method for preparing the negative electrode. The primer composition comprises a thickener containing one or more functional groups selected from hydroxyl groups and carboxyl groups, wherein the content of the residue of the thickener is less than 0.05 weight% relative to the total weight of the solid matter of the primer composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a primer composition, a negative electrode and a secondary battery comprising the primer composition, and a method for preparing the negative electrode. Background Art

[0002] With the development of electronics, communications and aerospace industries, the demand for lithium secondary batteries as energy sources is increasing dramatically. In particular, as the importance of global environmental protection policies is emphasized, the electric vehicle market is growing rapidly, and research and development related to lithium ion batteries are being actively carried out at home and abroad.

[0003] A lithium secondary battery includes a positive electrode (cathode), a negative electrode (anode), and a separator disposed therebetween. The positive electrode and the negative electrode each contain an active material that can insert and extract lithium ions.

[0004] In addition, when preparing the negative electrode, although the primer layer and the active material slurry layer can be coated in a wet-on-wet manner to improve the interfacial adhesion between the current collector and the active material slurry layer in the negative electrode, due to the low viscosity of the primer layer, various process defects may occur, such as cracks or pinholes on the electrode surface. Summary of the invention

[0005] Technical issues to be solved

[0006] The present invention provides a primer composition having a low occurrence rate of process failure and improved rapid charging performance, a negative electrode and a secondary battery comprising the primer composition, and a method for preparing the negative electrode.

[0007] Technical Solution

[0008] The primer composition according to the present invention comprises a thickener containing one or more functional groups selected from hydroxyl and carboxyl groups, wherein the content of the thickener residue is 0.05 wt % or less relative to the total solid weight of the primer composition.

[0009] According to an embodiment, the thickener may include at least one selected from carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, ethyl hydroxyethyl cellulose, methyl ethyl hydroxyethyl cellulose and cellulose gum.

[0010] According to an embodiment, the thickener may include carboxymethyl cellulose.

[0011] According to an embodiment, the degree of substitution of the thickener may be 0.5 to 1.0.

[0012] According to an embodiment, the weight average molecular weight of the thickener may be 300,000 to 500,000.

[0013] According to an embodiment, the viscosity of the primer composition (B-type viscometer, room temperature, 30 rpm) may be 20-5000 cps.

[0014] According to an embodiment, the primer composition may include a binder.

[0015] According to an embodiment, the adhesive may include styrene-butadiene rubber.

[0016] According to an embodiment, the adhesive may also include one or more selected from polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, styrene monomer (SM), butadiene (BD) and butyl acrylate (BA).

[0017] According to an embodiment, the primer composition may include one or more conductive materials selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, metal fiber, carbon fluoride, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives.

[0018] The negative electrode according to the present invention includes: a current collector; a primer layer located on the current collector and comprising the primer composition of the present invention; and a negative electrode active material layer located on at least a portion of the primer layer.

[0019] According to the embodiment, each 1×1 m 2 The number of pinholes per unit area may be 5 or less.

[0020] The secondary battery according to the present invention includes: a positive electrode, the negative electrode of the present invention, and a separator interposed between the positive electrode and the negative electrode.

[0021] The method for preparing a negative electrode according to the present invention comprises the following steps: (a) preparing a slurry containing a thickener containing one or more functional groups selected from hydroxyl groups and carboxyl groups; (b) filtering the slurry to prepare a primer composition; and (c) coating the primer composition on a current collector to form a primer layer, wherein the content of the residue of the thickener is less than 0.05 wt % relative to the total weight of the solid matter of the primer composition prepared in the step (b).

[0022] According to an embodiment, the step (a) may further include the step of mixing a styrene-butadiene rubber binder into the slurry.

[0023] According to an embodiment, in the step (b), the slurry may be filtered using a filter with 80-120 mesh.

[0024] According to an embodiment, the viscosity of the primer composition prepared in step (b) may be 20-5000 cps (B-type viscometer, room temperature, 30 rpm).

[0025] According to an embodiment, the step (c) may further include a step of coating a slurry including a negative active material on at least a portion of the primer layer to form a negative active material layer.

[0026] According to an embodiment, the negative active material layer may be formed on the primer layer in a wet-on-wet manner.

[0027] Beneficial Effects

[0028] The primer composition according to the present invention includes a thickener to enhance the cohesive force between the binders included in the primer composition, and thus can improve the problem of cracks generated on the electrode surface.

[0029] Furthermore, the primer composition according to the present invention can improve the problem of pinholes generated on the electrode surface centered on the thickener residues by reducing the thickener residue content in the primer composition.

[0030] In addition, the primer composition according to the present invention improves the problem of electrode detachment by improving the interface adhesion between the current collector and the electrode active material layer in the negative electrode, and thus can improve the resistance performance and fast charging performance of the secondary battery.

[0031] Furthermore, the secondary battery according to the present invention reduces the defective rate of products produced in the manufacturing process by improving the frequency of cracks generated on the electrode surface and the problem of pinholes, thereby ensuring product reliability. DETAILED DESCRIPTION

[0032] The description of the structure or function of the implementation scheme disclosed in this specification or this application is merely exemplified for the purpose of illustrating the implementation scheme according to the technical idea of ​​the present invention. The implementation scheme according to the technical idea of ​​the present invention may be implemented in various ways in addition to the implementation scheme disclosed in this specification or this application, and is not to be construed as limiting the technical idea of ​​the present invention to the implementation scheme described in this specification or this application.

[0033] Hereinafter, a primer composition, a negative electrode and a secondary battery including the primer composition, and a method for preparing the negative electrode according to the present invention are described.

[0034] <Primer Composition>

[0035] The primer composition according to the present invention comprises a thickener containing one or more functional groups selected from hydroxyl and carboxyl groups, wherein the content of the thickener residue is 0.05 wt % or less relative to the total solid weight of the primer composition.

[0036] Generally, with respect to the primer composition, in order to improve the problem of electrode detachment by improving the interfacial adhesion between the current collector and the electrode active material layer in the negative electrode, a primer layer containing the primer composition is formed on the current collector and then a slurry containing an active material is coated on the primer layer to prepare the negative electrode.

[0037] However, in a state where the primer composition is not dried after being applied, that is, in a state where the viscosity of the primer composition is low and the fluidity is high, when a high-density slurry is thickly applied on the applied primer layer, various process problems may occur. As a representative problem, there may be a process problem that the slurry is not applied in a desired amount due to the slip of the primer layer of the substrate at the moment of applying the slurry by slot extrusion coating, and in addition, due to the surface tension of the slurry and the high fluidity of the primer layer, a high-thickness edge ring problem may occur at the end of the electrode coating.

[0038] In addition, when the viscosity of the primer composition is low, the process failure is further aggravated. Generally, in order to coat the film, the binder solution is diluted to a low concentration and coated, so the failure may be more serious. Moreover, most of the binder in the electrode is located at the interface between the current collector and the negative electrode, so there is an effect of improving performance, but the problem of aggravated cracks on the surface of the negative electrode may occur during the drying process.

[0039] According to an embodiment, the primer composition of the present invention includes a thickener to reduce such process defects. The primer composition according to the present invention includes a thickener containing one or more functional groups selected from hydroxyl and carboxyl groups, and this thickener has the effect of enhancing the cohesion between the negative electrode active materials. By adding a thickener to the primer composition, the thickener enhances the cohesion at the interface between the layer with a high binder concentration and the layer with a low binder concentration, thereby significantly improving the problem of cracks on the electrode surface.

[0040] However, when a thickener is added to the primer composition to improve the problem of cracks on the electrode surface, pin-holes may be generated on the electrode surface due to a dewetting phenomenon caused by the residue of the thickener that is not dissolved in the primer composition.

[0041] According to the embodiment, in order to improve the problem of cracks on the electrode surface and the pinholes on the electrode surface, the primer composition of the present invention comprises less than 0.05% by weight of the residue of the thickener relative to the total weight of the solids of the primer composition. Preferably, the content of the residue of the thickener may be less than 0.04% by weight, less than 0.03% by weight or less than 0.02% by weight relative to the total weight of the solids of the primer composition. When the content of the residue of the thickener is higher than the above value, pinholes may be generated on the electrode surface centered on the residue of the thickener.

[0042] Specifically, the thickener residue refers to undissolved aggregates of the thickener contained in the primer composition. In addition, the undissolved aggregates of the thickener may refer to microgels of the thickener contained in the primer composition.

[0043] More specifically, the content of the residue of the thickener may be calculated according to Formula 1 below.

[0044] [Formula 1]

[0045] Thickener residue content (weight %) = (AB) / C × 100

[0046] In the formula 1,

[0047] A: represents the content of the thickener residue that has not been filtered after the primer composition is filtered through a filter with 80-120 mesh and dried at room temperature and the weight of the mesh filter,

[0048] B: indicates the weight of the mesh filter.

[0049] C: represents the weight of the primer composition filtered through the mesh filter×the solid content (weight %) of the primer composition.

[0050] As described above, the primer composition according to the present invention can improve pinhole defects on the electrode surface by removing the residue of the thickener contained in the primer composition using a mesh filter or the like or reducing the content of the residue of the thickener.

[0051] According to an embodiment, the solid content of the primer composition may be 15 wt % or more, 16 wt % or more, 17 wt % or more, 18 wt % or more, 19 wt % or more, or 20 wt % or more, and may be 30 wt % or less, 29 wt % or less, 28 wt % or less, 27 wt % or less, 26 wt % or less, or 25 wt % or less, for example, 15-30 wt %, 17-28 wt % or 20-25 wt %.

[0052] According to the embodiment, the solid content of the thickener may be 0.001 wt % or more, 0.005 wt % or more, 0.01 wt % or more, 0.05 wt % or more, or 0.1 wt % or more, and may be 3 wt % or less, 2.5 wt % or less, 2 wt % or less, 1.8 wt % or less, or 1.0 wt % or less, for example, 0.001-3.0 wt %, 0.005-2.5 wt %, 0.01-2 wt %, 0.05-1.8 wt % or 0.1-1.0 wt %. When the solid content of the thickener is lower than the above values, the process failure such as slippage of the above primer layer may occur due to the low viscosity of the primer composition. On the other hand, when the solid content of the thickener is too high, the content of the residue of the thickener increases, so pinholes may be generated after the electrode is coated.

[0053] According to an embodiment, the thickener may include one or more selected from carboxymethylcellulose (CMC), methylcellulose (MC), hydroxypropylcellulose (HPC), methylhydroxypropylcellulose (MHPC), ethylhydroxyethylcellulose (EHEC), methylethylhydroxyethylcellulose (MEHEC) and cellulose gum. Preferably, the thickener may include carboxymethylcellulose (CMC).

[0054] According to the embodiment, the degree of substitution of the thickener may be 0.5 or more, 0.55 or more, 0.6 or more, 0.65 or more, or 0.7 or more, and may be 1.0 or less, 0.95 or less, 0.9 or less, 0.85 or less, or 0.8 or less, for example, 0.5 to 1.0, 0.6 to 0.9, or 0.7 to 0.8. When the degree of substitution of the thickener is lower than the above values, due to the low water solubility, a large amount of thickener residues may be present when dissolved in distilled water, thereby pinholes may be generated on the electrode surface after coating. On the other hand, when the degree of substitution of the thickener is higher than the above values, the hydrophilicity is increased, so the solubility is increased, but the affinity with the active substance is reduced, so the problem of reduced adsorption may occur.

[0055] According to an embodiment, the weight average molecular weight (Mw) of the thickener may be 300,000 or more, 320,000 or more, 350,000 or more, or 380,000 or more, and may be 500,000 or less, 480,000 or less, 450,000 or less, or 420,000 or less, for example, 300,000 to 500,000, 350,000 to 450,000, or 380,000 to 420,000. The weight average molecular weight of the thickener may be measured by measuring the relative value relative to a standard polystyrene (PS) sample by gel permeation chromatography (GPC, waters breeze) using tetrahydrofuran (THF) as an eluent. When the weight average molecular weight of the thickener is lower than the above value, the attraction between the polymers forming the network is reduced when the thickener forms a network, so the negative electrode active material cannot be evenly dispersed, and the binding force of the active material decreases, which may have a negative impact on the life characteristics of the battery. On the other hand, when the weight average molecular weight of the thickener is higher than the above value, the viscosity of the slurry may increase to a level that is difficult to apply due to the excessively high viscosity at the same concentration. In order to prevent this problem, when distilled water is further added to reduce the viscosity, the solid content of the slurry is reduced, which may reduce the productivity of the electrode.

[0056] According to the embodiment, the viscosity (B-type viscometer, room temperature, 30rpm) of the primer composition of the present invention can be 20cps or more, 50cps or more, or 100cps or more, and can be 5000cps or less, 4000cps or less, 3000cps or less, or 2000cps or less, for example, 20-5000cps, 50-4000cps, or 100-2000cps. When the viscosity of the primer composition is lower than the above value, process defects such as slippage and edge rings of the primer layer may occur. On the other hand, when the viscosity of the primer composition is higher than the above value, pinholes are generated on the electrode surface due to the residue of the thickener, or it may be difficult to apply to the process due to the high viscosity.

[0057] According to an embodiment, the primer composition of the present invention may include an adhesive. In addition, the adhesive may include styrene-butadiene rubber. In addition, the adhesive may also include one or more selected from polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, styrene monomer (SM), butadiene (BD) and butyl acrylate (BA).

[0058] According to the embodiment, the solid content of the binder can be 15% by weight or more, 16% by weight or more, 18% by weight or more, or 20% by weight or more, relative to the total weight of the primer composition, and can be 30% by weight or less, 28% by weight or less, 26% by weight or less, or 24% by weight or less, for example, 15-30% by weight, 16-28% by weight, or 20-24% by weight. When the solid content of the binder is lower than the above value, the adhesion between the current collector and the active material or between the active materials is reduced, so the improvement effect of the fast charging performance may be weak. On the other hand, when the solid content of the binder is higher than the above value, the resistance in the electrode is increased, thereby reducing the characteristics of the battery, and the content of the active material and the conductive material is relatively reduced, so the capacity and conductivity of the electrode may be reduced. For example, the binder can use styrene-butadiene rubber with a solid content of 40%, a pH of 8, a particle size of 50-300nm, and a glass transition temperature (Tg) of -5°C to 10°C.

[0059] According to an embodiment, the primer composition according to the present invention may further include a component for forming a primer layer. For example, in order to improve conductivity, it may include one or more conductive materials selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, metal fiber, carbon fluoride, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenyl derivatives.

[0060] <Negative electrode>

[0061] The negative electrode according to the present invention includes: a current collector; a primer layer located on the current collector and comprising the primer composition of the present invention; and a negative electrode active material layer located on at least a portion of the primer layer.

[0062] According to the embodiment, the current collector is not particularly limited as long as it is a current collector that does not cause chemical changes in the secondary battery and has conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, fine concavoconvexity can be formed on the surface to enhance the binding force of the negative electrode active material, and it can be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven fabric, etc.

[0063] According to an embodiment, the primer layer includes a primer composition, and the primer composition may use the thickener, the content of the thickener residue, etc. described above in relation to the primer composition.

[0064] According to the embodiment, the thickness of the primer layer may be 0.1-10%, for example, 0.1-5.0 μm, and specifically 0.1-3.0 μm, based on the thickness of the negative electrode mixture layer.

[0065] According to the embodiment, in the negative electrode, when the negative electrode active material layer is located on the primer layer, the binder of the primer layer can be distributed in various forms. For example, the binder can be distributed adjacent to the current collector, or distributed inside the negative electrode active material layer by diffusion of the binder.

[0066] According to the embodiment, the primer layer and the negative electrode active material layer can be coated in a wet-on-wet manner by a slot-die coater, a roll-coater, a knife coater, an extrusion coater or a gravure-coater, thereby improving the interfacial adhesion between the current collector and the negative electrode active material layer, and improving the problem of electrode detachment, thereby improving the resistance performance and fast charging performance of the battery.

[0067] According to the embodiment, in the negative electrode according to the present invention, the number of pinholes per unit area may be 5 or less, 4 or less, 3 or less, or 1 or less. The number of pinholes is calculated by dividing 1×1 m 2 A quantity measured as a unit of area.

[0068] <Secondary Battery>

[0069] The secondary battery according to the present invention includes: a positive electrode, the negative electrode of the present invention, and a separator interposed between the positive electrode and the negative electrode.

[0070] According to the embodiment, the secondary battery includes a negative electrode, and the negative electrode may use the current collector, the primer layer, the negative electrode active material layer, and the like described above in relation to the negative electrode.

[0071] According to the embodiment, the secondary battery includes a positive electrode and a separator in addition to the negative electrode according to the embodiment of the present invention. The positive electrode and the negative electrode may include a current collector and an active material layer configured on the current collector, respectively. For example, the positive electrode may include a positive electrode current collector and a positive electrode active material layer, and the negative electrode may include a negative electrode current collector and a negative electrode active material layer. The active material layer may contain an active material. For example, the positive electrode active material layer may contain a positive electrode active material, and the negative electrode active material layer may contain a negative electrode active material. The positive electrode active material may be a material that allows lithium (Li) ions to be embedded and de-embedded.

[0072] According to the embodiment, the positive electrode active material may be a lithium metal oxide. For example, the positive electrode active material may be one of lithium manganese-based oxide, lithium nickel-based oxide, lithium cobalt-based oxide, lithium nickel manganese-based oxide, lithium nickel cobalt aluminum-based oxide, lithium iron phosphate-based compound, lithium manganese phosphate-based compound, lithium cobalt phosphate-based compound and lithium vanadium phosphate-based compound, and is not necessarily limited to a specific example.

[0073] According to the embodiment, the negative electrode active material may be a material that can embed and de-embed lithium ions. For example, the negative electrode active material may be any one of a carbon-based material such as crystalline carbon, amorphous carbon, a carbon composite, carbon fiber, a lithium alloy, silicon (Si), and tin (Sn). For example, the negative electrode active material may be natural graphite or artificial graphite, but is not limited to a specific example.

[0074] According to the embodiment, the separator can be between the positive electrode and the negative electrode. The separator is configured to prevent a short circuit between the positive electrode and the negative electrode and generate an ion flow. The separator may include a porous polymer film or a porous non-woven fabric. Among them, the porous polymer film may be composed of a single layer or multiple layers of polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. The porous non-woven fabric may include high-melting-point glass fibers, polyethylene terephthalate fibers. However, it is not limited thereto, and according to the embodiment, the separator may be a high-heat-resistant separator (ceramic coated separator, CCS) including ceramic.

[0075] According to the embodiment, an electrode cell including a positive electrode, a negative electrode and a separator may be provided. The electrode cell may be wound, laminated, folded or zigzag stacked, thereby providing an electrode assembly.

[0076] According to the embodiment, the electrode assembly is provided together with the electrolyte, so that the secondary battery according to the embodiment can be provided. The secondary battery may be any one of a cylindrical, rectangular, pouch, and coin type using a can, but is not limited thereto.

[0077] According to an embodiment, the electrolyte may be a non-aqueous electrolyte. The electrolyte may include a lithium salt and an organic solvent. The organic solvent may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), dipropyl carbonate (DPC), vinylene carbonate (VC), dimethyl sulfoxide (dimethyl sulfoxide), acetonitrile (acetonitrile), dimethoxyethane (dimethoxyethane), diethoxyethane (diethoxyethane), sulfolane (sulfolane), gamma-butyrolactone (gamma-butyrolactone), propylene sulfide (propylene sulfide) or tetrahydrofuran (tetrahydrofuran) at least one.

[0078] <Method for preparing negative electrode>

[0079] The method for preparing a negative electrode according to the present invention comprises the following steps: (a) preparing a slurry containing a thickener containing one or more functional groups selected from hydroxyl groups and carboxyl groups; (b) filtering the slurry to prepare a primer composition; and (c) coating the primer composition on a current collector to form a primer layer, wherein the content of the residue of the thickener is less than 0.05 wt % relative to the total weight of the solid matter of the primer composition prepared in the step (b).

[0080] According to an embodiment, the preparation method comprises the following steps: (a) preparing a slurry containing a thickener containing one or more functional groups selected from hydroxyl and carboxyl groups. In addition, the step (a) may further comprise the step of mixing a styrene-butadiene rubber binder into the slurry.

[0081] According to the embodiment, the thickener and the binder may be the same types of thickener and binder as those described above with respect to the primer composition.

[0082] According to an embodiment, the preparation method includes the following steps: (b) filtering the slurry to prepare a primer composition.

[0083] According to an embodiment, the slurry can be filtered using a filter with a mesh size of 80-120 in step (b). In the step of filtering the slurry to prepare the primer composition, a mesh filter, for example, a 120-mesh (mesh size of 210 μm) filter is used to remove the residue of the thickener contained in the primer composition or reduce the content of the residue of the thickener, thereby improving the pinhole defect on the electrode surface.

[0084] According to the embodiment, the viscosity (B-type viscometer, room temperature, 30rpm) of the primer composition prepared in the step (b) may be 20-5000cps. When the viscosity of the primer composition is lower than the above value, the process of coating the primer composition on the current collector may cause slippage of the primer layer, edge rings and other process defects. On the other hand, when the viscosity of the primer composition is higher than the above value, pinholes are generated on the electrode surface due to the residue of the thickener, or due to the high viscosity, it may be difficult to apply to the process.

[0085] According to an embodiment, the content of the thickener residue is 0.05 wt % or less relative to the total weight of the solid content of the primer composition prepared in step (b). The content of the thickener residue can also be calculated by formula 1 in the above description of the thickener residue.

[0086] According to an embodiment, the preparation method includes the following steps: (c) coating the primer composition on a current collector to form a primer layer. In addition, step (c) may further include coating a slurry containing a negative electrode active material on at least a portion of the primer layer to form a negative electrode active material layer.

[0087] The negative electrode active material layer may be formed on the primer layer by a known method, preferably a wet-on-wet method. For example, the negative electrode active material layer is formed after the primer composition is applied to the current collector without being dried, and the negative electrode active material layer may be applied on the primer layer by a slit extrusion coater, a roll coater, a blade coater, an extrusion coater or a gravure coating machine in a wet-on-wet manner.

[0088] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples. However, the following Examples and Comparative Examples are merely illustrative for describing the present invention in more detail, and the present invention is not limited to the following Examples and Comparative Examples.

[0089] Example

[0090] <Preparation of Primer Composition>

[0091] Example 1

[0092] Carboxymethyl cellulose (CMC, degree of substitution of 0.7, weight average molecular weight of 400000) as a thickener is dissolved in pure water to make the solid content of 0.6% by weight, thereby preparing a CMC solution. The prepared CMC solution is mixed with a suspension of styrene-butadiene rubber (SBR, solid content of 40% by weight, pH of 8, particle size of 150nm, Tg of 2°C) as a binder to prepare a mixture. Thereafter, the mixture is filtered using a filter, and the residue of the thickener is removed to prepare a primer composition. The SBR solid content, CMC solid content, filter size, number of filtrations and solid content in the primer composition prepared are recorded in Table 1 below.

[0093] Examples 2 to 5 and Comparative Examples 1 to 3

[0094] A primer composition was prepared by the same process as in Example 1 except that the SBR solid content, CMC solid content, filter size, number of filtrations, and solid content in the primer composition described in Table 1 below were used.

[0095] <Measurement of Viscosity of Primer Composition>

[0096] The viscosity of the primer compositions of Examples 1 to 5 and Comparative Examples 1 to 3 was measured at 30 rpm using a Brookfield viscometer and a No. 5 rotor at room temperature and is shown in Table 1 below.

[0097] <Calculation of the content of residual thickener>

[0098] A mesh filter with a mesh size of 120 is prepared into a cone with a diameter of 50 mm, and then 100 g of each primer composition prepared in Examples 1 to 5 and Comparative Examples 1 to 3 is passed through the mesh filter by gravity, and the residue on the top of the mesh filter is dried at room temperature for 4 hours. At this time, the weight of the mesh filter before and after filtration is measured, and the content of the residue of the thickener CMC relative to the total weight of the solids of the primer composition is calculated according to the following formula 2. The content of the residue of the thickener CMC relative to the total weight of the solids of the primer composition of Examples 1 to 5 and Comparative Examples 1 to 3 is recorded in Table 1 below.

[0099] [Formula 2]

[0100] The residual content of the thickener relative to the total weight of the solid content of the primer composition (weight %) = (AB) / C × 100

[0101] In the formula 2,

[0102] A: The weight of the mesh filter after filtration

[0103] B: Weight of the mesh filter before filtration

[0104] C: Weight of filtered primer composition x solid content of primer composition (wt%)

[0105] [Table 1]

[0106]

[0107]

[0108] Experimental example

[0109] Experimental Example 1-Evaluation of Negative Electrode Quality

[0110] <Preparation of negative electrode>

[0111] A negative electrode active material of artificial graphite (D50: 13 μm) and natural graphite (D50: 10 μm) mixed in a weight ratio of 5:5, a CMC thickener, and an SBR binder in a weight ratio of 98.5:1:0.5 were added to water to prepare a negative electrode slurry with a viscosity of 5000 cps.

[0112] Using a gravure coating machine and a slot die coating machine, the primer composition and the negative electrode slurry prepared in Example 1 were coated on one side of a copper current collector (copper foil with a thickness of 8 μm) with a thickness of 1 μm and 200 μm, respectively, and then dried, and the other side was also coated in the same manner and then dried.

[0113] The dried negative electrode was pressed (pressing density: 1.68 g / cm 3 ), thereby preparing a negative electrode having a negative electrode active material layer formed thereon. At this time, the thickness of the prepared negative electrode was 127 μm.

[0114] In the same manner as the process of preparing a negative electrode using the primer composition prepared in Example 1, negative electrodes having a thickness of 127 μm were prepared using the primer compositions prepared in Examples 2 to 5 and Comparative Examples 1 to 3, respectively.

[0115] <Measurement of the number of pinholes in the negative electrode>

[0116] For each of the above negative electrodes, the negative electrode was visually observed for every 1 m 2 The number of pinholes with an area diameter of 200 μm or more was observed 5 times in total, and the average number of pinholes was calculated as the number of negative electrode pinholes and recorded in Table 2 below.

[0117] <Measurement of Negative Electrode Crack Frequency>

[0118] For each of the above negative electrodes, the negative electrode was visually observed for every 1 m 2 The number of cracks with an area length of 5 mm or more and a depth of 20 μm or more was observed 5 times in total, and the average number of negative electrode cracks was calculated as the negative electrode crack frequency and recorded in Table 2 below.

[0119] [Table 2]

[0120]

[0121] Experimental Example 2-Evaluation of Battery Performance

[0122] <Preparation of positive electrode>

[0123] As the positive electrode active material, Li[Ni 0.88 Co 0.1 Mn 0.02 ]O2, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in a weight ratio of 96.5:2:1.5 to prepare a slurry. The slurry was uniformly coated on an aluminum foil with a thickness of 12 μm and vacuum dried to prepare a positive electrode.

[0124] <Preparation of Secondary Battery>

[0125] The prepared positive electrode and the negative electrode prepared using the primer composition prepared in Example 1 are cut (Notching) and stacked in a specified size, and a separator (polyethylene, 13 μm thick) is inserted between the positive electrode and the negative electrode to form an electrode unit, and then the tabs of the positive electrode and the negative electrode are welded respectively. The welded positive electrode / separator / negative electrode assembly is placed in a soft bag, and the three surfaces except the electrolyte injection surface are sealed. At this time, the portion with the tab is included in the sealing portion.

[0126] The electrolyte was injected through the remaining surfaces except the sealing part, and the remaining surfaces were sealed, and then immersed for more than 12 hours. The electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of EC / EMC / DEC (25 / 45 / 30, volume ratio) and then adding 1 wt% vinylene carbonate (VC), 0.5 wt% 1,3-propylene sultone (PRS) and 0.5 wt% lithium bis(oxalatoborate) (LiBOB).

[0127] After that, pre-charging was performed for 36 minutes at a current corresponding to 0.25C. Degassing was performed after 1 hour, and aging was performed for more than 24 hours, and then formation charge and discharge were performed (charging conditions were CC-CV0.2C 4.2V 0.05C cut-off, and discharge conditions were CC 0.2C 2.5V cut-off). After that, standard charge and discharge were performed to prepare a secondary battery (charging conditions were CC-CV 0.33C 4.2V 0.05C cut-off, and discharge conditions were CC 0.33C 2.5V cut-off).

[0128] Secondary batteries were prepared using the primer compositions of Examples 2 to 5 and Comparative Examples 1 to 3, respectively, by the same method as the preparation process of the secondary battery using the primer composition of Example 1.

[0129] <Measurement of resistance value of secondary battery>

[0130] The prepared secondary batteries were fully charged (charging conditions were CC-CV 0.33C 4.2V 0.05C cut-off), and then half of the discharge capacity under standard charge and discharge was discharged at a current of 0.33C (I0), and then the voltage (V0) was measured at a SOC of 50% after standing (rest) for 1 hour. In addition, the prepared secondary battery with an SOC of 50% was discharged at a rate of 1.0C for 10 seconds and then the termination voltage (V1) was measured. The resistance value (mΩ) of the secondary battery under the condition of 1.0C discharge for 10 seconds at 50% SOC was measured according to the following formula 3 and recorded in the following Table 3.

[0131] [Formula 3]

[0132] Resistance value of secondary battery (mΩ) = (V1-V0) / (I0)

[0133] <Measurement of Voltage Value of Secondary Battery after 5 Rapid Charges>

[0134] Each of the prepared secondary batteries was charged from 8% SOC to 80% SOC under the condition of rapid charging for 20 minutes at room temperature, and discharged at a current of 0.33 C, and the above steps were cycled 5 times. The voltage value (V) of the secondary battery after rapid charging 5 times was measured and recorded in the following Table 3.

[0135] [Table 3]

[0136]

[0137]

[0138] According to Tables 1 to 3, it can be confirmed that in the case of Examples 1 to 5 using a primer composition having a residual content of a thickener of 0.05 wt % or less relative to the total weight of the solids of the primer composition, the number of pinholes and the frequency of cracks in the negative electrode are significantly reduced compared to Comparative Examples 1 to 3. In addition, in the case of Examples 1 to 5, it can be confirmed that since pinholes and cracks are not generated in the negative electrode, the resistance value of the secondary battery is lower than that of Comparative Examples 1 to 3. In addition, in the case of Examples 1 to 5, it can be confirmed that the voltage value of the secondary battery after 5 rapid charges is lower than that of Comparative Examples 1 to 3, and thus has significant rapid charging performance.

[0139] On the other hand, in the case of Comparative Example 1 which does not contain a thickener, cracks in the negative electrode were confirmed, and in the cases of Comparative Examples 2 and 3 which contained a thickener but the content of the thickener residue relative to the total weight of the solid matter of the primer composition exceeded 0.05 wt %, it was confirmed that a large number of pinholes were generated in the negative electrode, and the resistance value of the secondary battery and the voltage value after rapid charging 5 times were high, thereby significantly reducing the quality of the negative electrode and the battery performance of the secondary battery.

Claims

1. A primer composition for preparing a negative electrode, the primer composition comprising a thickener containing one or more functional groups selected from hydroxyl and carboxyl groups, in, The content of the undissolved residue of the thickener is 0.05 wt % or less relative to the total weight of the solid content of the primer composition. The degree of substitution of the thickener is 0.5 to 1.0, Wherein, relative to the total weight of the primer composition, the solid content of the thickener is 0.001 wt % to 3.0 wt %, The thickener comprises at least one selected from carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, ethyl hydroxyethyl cellulose, methyl ethyl hydroxyethyl cellulose and cellulose gum, The weight average molecular weight of the thickener is 300,000 to 500,000. Wherein, under the conditions of a B-type viscometer, room temperature and 30 rpm, the viscosity of the primer composition is 20-5000 cps, Wherein, relative to the total weight of the primer composition, the solid content of the primer composition is 15 wt % to 30 wt %, and The content of the undissolved residue of the thickener is calculated according to the following formula 1: [Formula 1] Content of undissolved residue of thickener (weight %) = ((AB) / C) × 100 In the formula 1, A: represents the content of the undissolved residue of the thickener after filtering the primer composition through a 80-120 mesh filter and drying at room temperature and the weight of the mesh filter. B: indicates the weight of the mesh filter. C: represents the weight of the primer composition filtered by the mesh filter×the solid content of the primer composition expressed in weight %.

2. The primer composition according to claim 1, wherein The thickener comprises carboxymethyl cellulose.

3. The primer composition according to claim 1, wherein The primer composition comprises a binder.

4. The primer composition according to claim 3, wherein The adhesive comprises styrene-butadiene rubber.

5. The primer composition according to claim 4, wherein The adhesive further comprises one or more selected from polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber, fluororubber, styrene monomer, butadiene and butyl acrylate.

6. The primer composition according to claim 1, wherein The composition comprises one or more conductive materials selected from natural graphite, artificial graphite, carbon black, carbon fiber, metal fiber, carbon fluoride, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenyl derivatives.

7. A negative electrode, comprising: current collector; a primer layer, which is located on the current collector and comprises the primer composition of claim 1; as well as A negative electrode active material layer is located on at least a portion of the primer layer.

8. The negative electrode according to claim 7, wherein Each 1×1m 2 The number of pinholes per unit area is 5 or less.

9. A secondary battery comprising: positive electrode; The negative electrode according to claim 7; as well as A separator is disposed between the positive electrode and the negative electrode.

10. A method for preparing a negative electrode, comprising the following steps: (a) preparing a slurry containing a thickener having one or more functional groups selected from a hydroxyl group and a carboxyl group; (b) filtering the slurry to prepare a primer composition; as well as (c) coating the primer composition on a current collector to form a primer layer, Wherein, the content of the undissolved residue of the thickener is less than 0.05 wt % relative to the total weight of the solid matter of the primer composition prepared in the step (b), The degree of substitution of the thickener is 0.5 to 1.0, Wherein, relative to the total weight of the primer composition, the solid content of the thickener is 0.001 wt % to 3.0 wt %, The thickener comprises at least one selected from carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, ethyl hydroxyethyl cellulose, methyl ethyl hydroxyethyl cellulose and cellulose gum, The weight average molecular weight of the thickener is 300,000 to 500,000. Wherein, under the conditions of a B-type viscometer, room temperature and 30 rpm, the viscosity of the primer composition is 20-5000 cps, Wherein, relative to the total weight of the primer composition, the solid content of the primer composition is 15 wt % to 30 wt %, and The content of the undissolved residue of the thickener is calculated according to the following formula 1: [Formula 1] Content of undissolved residue of thickener (weight %) = ((AB) / C) × 100 In the formula 1, A: represents the content of the undissolved residue of the thickener after filtering the primer composition through a 80-120 mesh filter and drying at room temperature and the weight of the mesh filter. B: indicates the weight of the mesh filter. C: represents the weight of the primer composition filtered by the mesh filter×the solid content of the primer composition expressed in weight %.

11. The method for preparing a negative electrode according to claim 10, wherein: The step (a) further comprises the step of mixing a styrene-butadiene rubber binder into the slurry.

12. The method for preparing a negative electrode according to claim 10, wherein: The step (c) further includes applying a slurry containing a negative electrode active material on at least a portion of the primer layer to form a negative electrode active material layer.

13. The method for preparing a negative electrode according to claim 12, wherein: The negative electrode active material layer is formed on the primer layer in a wet-on-wet manner.

Citation Information

Patent Citations

  • Positive pole piece containing high-safety thermosensitive coating and lithium ion battery

    CN113764612A